Deterioration mechanism of mechanical properties of phosphorite under different saturation duration - Li, Shujian; Wang, Chongyang; Zhang, Dongming; Wang, Menglai; Zhou, Fan; Pan, Yisha (Frontiers in Earth Science, 2023)
In this paper, the degradation mechanism of phosphoric rock samples under different saturation duration was analyzed by laboratory test, theoretical analysis and neural network modeling, and the results is as follows: Saturation of water will result in deterioration of mechanical properties of samples. The peak compressive strength and peak strain of the samples decreased gradually with the increase of saturation time. The average peak strength of 12 h, 24 h, and 36 h saturated specimens is 8.6%, 21.1%, and 32.2% lower than that of natural specimens, and the peak strain is 5.9%, 13.9%, and 31.3% lower, respectively. The stress-strain curves of the samples with water saturation for 36 h have more jitter stages after the peak, indicating that the plastic characteristics of the samples will be increased with water saturation for a long time. The neural network method was used to analyze the test parameters and the mechanical parameters of the samples, and the mechanical properties under the action of saturated water and confining pressure were obtained. The neural network model was established to represent the mechanical properties of the samples, and the average accuracy of the model was 0.89. The model can be used to predict and verify the mechanical properties of samples under other saturation and confining pressure conditions in the limited region. The research results can provide theoretical reference for the deterioration mechanism of confining pressure in water-rich roadway.